2019
DOI: 10.26434/chemrxiv.9985205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Origins of Negative and Positive Electromechanical Response of Oligopeptide Piezoelectrics

Abstract: In response to an applied electric field, materials and even individual molecules can exhibit electromechanical response. Previous work has demonstrated the piezoelectric distortion of polar organic crystals, biomaterials, and even single molecular monolayers, increasing length in response to the change in potential energy of interaction between the polarization or dipole moment and the applied electric field. In this work, we demonstrate through density functional calculations that helical oligopeptides, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Piezoelectric materials have long been utilised for their ability to linearly interconvert electrical and mechanical energy. In recent years, there has been a large increase in the number of biomoleculebased materials demonstrating this phenomenon, from amino acids (Lemanov, 2000;Guerin et al, 2018a) and peptides (Baptista et al, 2019;Gayatri and Hutchison, 2019;Basavalingappa et al, 2020) to globular (Stapleton et al, 2017) and transmembrane proteins (O'Donnell et al, 2021), viruses (Lee et al, 2012), plants (Alluri et al, 2020), and food waste (Ghosh and Mandal, 2017;Ghosh et al, 2021). While a number of these materials rival established inorganic piezoelectrics such as aluminium nitrate (AlN) (Supryadkina et al, 2014) and zinc oxide (ZnO) (Kobiakov, 1980), few have demonstrated piezoelectric strain constants that can rival ceramics such as barium titanate (BaTiO3), lead zirconium titanate (PZT), and lead-free counterparts (Panda and Sahoo, 2015;Bell and Deubzer, 2018) for traditional sensing and actuating applications.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric materials have long been utilised for their ability to linearly interconvert electrical and mechanical energy. In recent years, there has been a large increase in the number of biomoleculebased materials demonstrating this phenomenon, from amino acids (Lemanov, 2000;Guerin et al, 2018a) and peptides (Baptista et al, 2019;Gayatri and Hutchison, 2019;Basavalingappa et al, 2020) to globular (Stapleton et al, 2017) and transmembrane proteins (O'Donnell et al, 2021), viruses (Lee et al, 2012), plants (Alluri et al, 2020), and food waste (Ghosh and Mandal, 2017;Ghosh et al, 2021). While a number of these materials rival established inorganic piezoelectrics such as aluminium nitrate (AlN) (Supryadkina et al, 2014) and zinc oxide (ZnO) (Kobiakov, 1980), few have demonstrated piezoelectric strain constants that can rival ceramics such as barium titanate (BaTiO3), lead zirconium titanate (PZT), and lead-free counterparts (Panda and Sahoo, 2015;Bell and Deubzer, 2018) for traditional sensing and actuating applications.…”
Section: Introductionmentioning
confidence: 99%